2023
DOI: 10.1002/ajmg.a.63322
|View full text |Cite
|
Sign up to set email alerts
|

Exome sequencing in a Romanian Bardet‐Biedl syndrome cohort revealed an overabundance of causal BBS12 variants

Abstract: Bardet‐Biedl syndrome (BBS), is an emblematic ciliopathy hallmarked by pleiotropy, phenotype variability, and extensive genetic heterogeneity. BBS is a rare (~1/140,000 to ~1/160,000 in Europe) autosomal recessive pediatric disorder characterized by retinal degeneration, truncal obesity, polydactyly, cognitive impairment, renal dysfunction, and hypogonadism. Twenty‐eight genes involved in ciliary structure or function have been implicated in BBS, and explain the molecular basis for ~75%–80% of individuals. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…To date, 28 genes have been reported to be associated with BBS phenotypes ( Niederlova et al, 2019 ; Gnanasekaran et al, 2023 ; Khan et al, 2023 ). Unlike Caucasian patients with higher proportions of BBS1 and BBS10 ( Niederlova et al, 2019 ; Melluso et al, 2023 ), we noted that BBS7 was the prominent genotype, followed by BBS2 , BBS10 , BBS12 , and BBS1 in these Chinese seies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, 28 genes have been reported to be associated with BBS phenotypes ( Niederlova et al, 2019 ; Gnanasekaran et al, 2023 ; Khan et al, 2023 ). Unlike Caucasian patients with higher proportions of BBS1 and BBS10 ( Niederlova et al, 2019 ; Melluso et al, 2023 ), we noted that BBS7 was the prominent genotype, followed by BBS2 , BBS10 , BBS12 , and BBS1 in these Chinese seies.…”
Section: Discussionmentioning
confidence: 99%
“…BBS is a ciliopathy and has been shown to be closely related to dysfunction of immotile cilia. To date, 28 genes have been reported to be associated with the BBS phenotypes, including 2 candidate genes ( SCLT1 and SCAPER ) and 2 contributors ( NPHP1 and TTC21B ) ( Niederlova et al, 2019 ; Khan et al, 2023 ; Gnanasekaran et al, 2023 ). In comparison, pathogenic variants in the BBS genes involved in encoding the BBSome complex, including BBS1 (OMIM 209901), BBS2 (OMIM 606151), BBS4 (OMIM 600374), BBS5 (OMIM 603650), BBS7 (OMIM 607590), BBS8/ TTC8 (OMIM 615985), and BBS9/PTHB1 (OMIM 607968), were the most common, followed by BBS genes involved in encoding BBSome complex “chaperone-like” proteins, including BBS6/ MKKS (OMIM 604896), BBS10 (OMIM 610148) , and BBS12 (OMIM 610683) ( Seongjin et al, 2009 ; Dai et al, 2022 ; Melluso et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, we found that BBS7 is the most common gene (5/11) involved in Chinese patients, followed by BBS2 and IFT74, inconsistent with other studies. Khan et al 14…”
Section: Discussionmentioning
confidence: 99%